Empagliflozin Managed Type 2 Diabetes Mellitus in Insulin induced Hypertension: A case report - Raja A; Sadagoban GK; Jemi Rachel Shaji; Renita Castelino; Swathi Swaroopa Borra (Journal of Global Pharma Technology, 2020)
Insulin is an essential hormone and has been the cornerstone in the therapy of Diabetes Mellitus. This case highlights insulin-induced hypertension in a type 2 DM patient, managed adequately with empagliflozin. A 60-year female with Diabetic Nephropathy & Hypothyroidism presented with elevated blood pressure after a week of insulin administration. An elevation in the patient’s blood pressure corresponding to the administration of insulin was observed. De-challenge and re-challenge of insulin with dose adjustment, resulted in sudden spike & decrease of blood pressure, thereby pointing a suspicion towards a relation between insulin and hypertension. Discontinuation of insulin and replacement with oral hypoglycemics has resulted in controlled blood pressure levels.